4. Calculează:
a) 3+ (-2)-5;
e) |-3| + |2|;
c) 5: (-5)+(-5);
d) (-2)³ - (-2)²2;
b) 6-(-2)•(-3);
f)|-5|-|-7|;
g) |(-2)²|-|(-2)³; h) ||−4|- |+6||;
i) −1 + 3 · {−3 − 2 · [− 1 − (5-3)]}²; j) [(−3− 1)² +3 · (−4) + (−2)³ +3 · (−1)4]³.
h) ||-4|-|+6|| urgenttt
Răspunsuri la întrebare
Răspuns:
a) 3 + (-2) - 5 = -4
e) |-3| + |2| = 5
c) 5 : (-5) + (-5) = -6
d) (-2)³ - (-2)²·2 = -16
b) 6 - (-2) • (-3) = 0
f) |-5| - |-7| = -2
g) |(-2)²| - |(-2)I³ = -12
h) ||−4|- |+6|| = 2
i) −1 + 3 · {−3 − 2 · [− 1 − (5-3)]}² = 26
j) [(−3− 1)² +3 · (−4) + (−2)³ +3 · (−1)4]³ = - 4096
Explicație pas cu pas:
a) 3 + (-2) - 5 = 3 - 2 - 5 = -4
e) |-3| + |2| = 3 + 2 = 5
c) 5 : (-5) + (-5) = -1 - 5 = -6
d) (-2)³ - (-2)²·2 = -8 - 4·2 = -8 - 8 = -16
b) 6 - (-2) • (-3) = 6 - 6 = 0
f) |-5| - |-7| = 5 - 7 = -2
g) |(-2)²| - |(-2)I³ = 4 - 8 = -12
h) ||−4|- |+6|| = I 4 - 6 I = I -2 I = 2
i) −1 + 3 · {−3 − 2 · [− 1 − (5-3)]}² = -1 + 3·{- 3 - 2·[-1 -2]}²
= -1 + 3·[- 3 - 2·(-3)]² = -1 + 3 (-3 + 6)²
= -1 + 3·3²
= -1 +27
= 26
j) [(−3− 1)² +3 · (−4) + (−2)³ +3 · (−1)4]³ = [(-4)² - 12 - 8 -12]³
= (16 - 32)³
= (-16)³
= - 4096